National and state representative youth athletes exhibit positive differences on a physical test battery within a school-based sports academy - Vallance, B.; Berry, J.; Carroll, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Reporting of physical test scores and anthropometric measures is common in sports research with examples in Australian football and Rugby League (Veal, Pearce & Carlson, 2010; Gabbett, 2002). However, there is little research available that looks across multiple sports and talent levels in an effort to inform coaches and sport scientists of both emerging and benchmark performance levels. Profiling elite level youth athletes can assist the formulation of age-appropriate performance benchmarks that can be subsequently used for coaching or talent identification purposes (Cullen et al., 2013). The purpose of this study was to establish if national and state level student-athletes across a range of sports exhibit distinct fitness and anthropometric profiles compared to the wider sports academy cohort. Methods: Participants included 153 male (13-16yrs) and 108 female (13-16years) student-athletes in total with 30 male and 41 female athletes subsequently identified as either a national and/or state representative for their sport. Twenty-seven sports were represented in this sample. The test battery consisted of height and weight, vertical jump, 20m speed test, and the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT1). Data was collected as part of routine testing during the athlete development program at the sports academy. Results: Separate ANOVA`s were conducted to negate any gender influence. In the male data, there was a significant main effect for group with bodyweight higher for the representative group. Positive trends were exhibited across the remaining variables for height, vertical jump, 20m Speed, and YYIRT1. There was no significant main-effect for group in the female data although positive trends were exhibited across all variables for height, weight, vertical jump, 20m Speed, and YYIRT1. Discussion: The results indicate national and state representative athletes exhibit positive differences on physical test battery scores compared to the wider sports academy cohort. While these differences were not pronounced, with the exception of bodyweight, they were consistent across all tests and across gender. Conversely, the results highlight the academy athletes as a whole are relatively homogenous in relation to the physical test battery scores. This is to be somewhat expected as athletes apply to the academy via a talent identification process and all participate in the athlete development program which includes physical preparation. Future research should explore the technical and tactical areas of performance to maximise any benchmarking exercise. This study provides a framework for coaches and sport scientists to develop age-appropriate performance benchmarks.